2013
DOI: 10.1177/0266666912461265
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility and facilities for the disabled in public and university library buildings in Iran

Abstract: The study examines the views of architect experts and physically disabled users on the accessibility status of 14 public and university library buildings in Iran. The respondents rated on the availability of items listed in a checklist grouped under five categories: parking, ramps, interior layout, exclusive space and public space for the disabled. The checklist was based on the American Disability Act and International Federation of Library Associations and Institutions checklist for libraries for the disable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 19 publications
5
30
0
Order By: Relevance
“…A study by Bodaghi and Zainab (2013) indicated that both architects and people with disabilities rated accessibility of the public and university library buildings in Zanjan province in Iran as "not good enough". Todaro (2005) in Argentina and Koulikourdi (2008) in Greece have likewise shown that much more needs to be done if libraries in their countries are to be described as truly accessible to people with disabilities.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Bodaghi and Zainab (2013) indicated that both architects and people with disabilities rated accessibility of the public and university library buildings in Zanjan province in Iran as "not good enough". Todaro (2005) in Argentina and Koulikourdi (2008) in Greece have likewise shown that much more needs to be done if libraries in their countries are to be described as truly accessible to people with disabilities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The right to access facilities, information sources and services without any hindrance is one of the fundamental rights a society should protect, especially for people with disabilities (Bodaghi & Zainab 2013). In light of this statement, the present study explored accessibility of library buildings to people with disabilities.…”
Section: Accessibility Of Library Buildings To People With Disabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings concur with those of Ndumbaro (2009) who says that the national policy is not clear on the availability of library and information services. In the same vein, Bath (2005), cited in Bodaghi and Zainab (2012), claims that there is a lack of policies, procedures or guidelines that cater for the needs of people with disabilities. UNESCO (1997) asserts that only a few universities have a written policy regarding disabled students.…”
Section: Policy Environmentmentioning
confidence: 99%
“…This problem should be resolved. Barriers on the roads and accessibility to public institution facilities, schools, faculties, banks, health institutions, theatres, museums, but also to residential buildings and houses must be identified and removed, as noted by many researchers (Bodaghi & Zainab, 2012;Chiwandire & Vincent, 2017). The results of our study show that about 80.0% of the examined institutions in Novi Sad are not at ground level (80.8% of educational and 79.3% of public institutions), which entails the obligation for them to ensure fulfilment of the required accessibility elements, in this case, ramps.…”
Section: Discussionmentioning
confidence: 99%